Hubungan Antara Komunikasi Interpersonal Dosen Dengan Prestasi Akademik Mahasiswa - Safitri, Rika; Issroviatiningrum, Retno; Abdurrouf, Muh (Journal of Nursing Invention, 2025)
Background: Academic achievement reflects the success of higher education. However, data from LLDIKTI Region VI Central Java (2022) showed a decline in the average GPA of nursing students at several private universities, including Sultan Agung Islamic University (UNISSULA) Semarang. This raises concerns about the effectiveness of the learning process. One factor that may influence academic performance is the quality of interpersonal communication between lecturers and students. Effective communication, involving the exchange of information, feelings, and meaning, is essential in creating a supportive learning environment. Objective: This study aimed to examine the relationship between lecturers’ interpersonal communication skills and students’ academic performance at UNISSULA. Method: A quantitative cross-sectional design was used, involving 122 undergraduate nursing students from the 2023 cohort selected through simple random sampling. Data were collected using a 14-item interpersonal communication questionnaire and analyzed with Spearman’s rank correlation. Result: The results showed that 59% of students rated lecturers’ communication as very good, and 49.2% had high GPAs. A significant correlation was found (p = 0.001) Conclusion: Interpersonal communication of lecturers is important to enhance students' motivation, understanding, and engagement. Therefore, communication training is necessary to support the quality of education and academic achievement.